Allelic polymorphism of atoxigenic Vibrio Cholerae strains of housekeeping genes isolated in Siberia and Far East - E. G. Goldapel; L. V. Mironova; M. V. Afanas'ev; S. V. Balakhonov (Acta Biomedica Scientifica, 2013)
There were atoxigenic Vibrio cholerae strains housekeeping genes analyzed. There were studied 20 isolates, in which nine sequence types have determined and five of which have described as unique. There were clustersformed as belonging to serogroup: first cluster includes RO-variantstrains and one O139 serogroup strain of V. cholerae, second - all O1 serogroup V. cholerae strains. There are sequence types associated with place and time isolation strains in some cases, although differentiation of the strains, which are formed the dominant sequence type strains group have no spatial and temporal characteristics associated.